The effect of nursing shared governance educational program on nurse managers’ knowledge for sustainable nursing excellence and empowerment - Sally Mohammed Farghaly Abdelaliem; Khalid Al-Mugheed; Majdi M. Alzoubi; Islam Al-Oweidat; Ghada Mohamed Hamouda (PLoS ONE, 2025)
Background Nursing governance residues one of the most composite functions in the complex and complicated healthcare arena. Providing nurse managers with professional nursing governance knowledge and its related practices is essential in today’s competitive healthcare environment for nursing practices excellence. Objective This research aimed to determine the effect of Professional Nursing Shared Governance Awareness Sessions on First-Line Nurse Managers’ Knowledge. Design A quasi-experimental research design. Setting Alexandria Medical Research Institute hospital. Participants A total of 50 first-line nurse managers were recruited for the participating hospital. Methods Professional Nursing Shared Governance Knowledge Questionnaire and the participants’ socio-demographic characteristics questions were included. Results There was a statistically significant differences between the overall mean score of first-line nurse managers’ knowledge about professional nursing shared governance before and after attending nursing shared governance awareness sessions (p < 0.001). The overall mean score of professional nursing shared governance was increased significantly from 3.12 ± 2.54 to 5.86 ± 0.35 (t 7.493, p < 0.001). Conclusions This research plugs the Arabian nursing literature gap by representing how effective professional nursing shared governance awareness sessions could improve the nurse managers’ level of knowledge regarding the governance concept and its practices. Participants perceived the awareness sessions as constructive and strategic contrivances to determine and evolve high-potential personnel in opportunities as giving compassionate organizational structures and effective leadership behaviors for aggregating contribution of nurses in work enterprise, problem-solving, conflict resolution, teams and organizational decision-making as “crucial components to an efficacious organization”. Hence, the definitive issue for the nursing profession future is participative decision making through shared governance, as it should be a part of every organization’s strategic plan.